Penyuluhan “CERDIK” (Cek Kesehatan Secara Rutin) Sebagai Upaya Pengendalian Penyakit Tidak Menular - Hamid, Abdul; Putri Adekayanti (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Non-communicable diseases (PTM) are diseases that kill around 41 million people every year, equivalent to 74% of all deaths globally. Every year around 17 million people die from NCD before the age of 70, of which 86% of these premature deaths occur in low- and middle-income countries (World Health Organization, 2023). PTM risks threaten everyone of all age groups, regions and countries affected by PTM. Indonesia is facing an epidemiological transition in health problems, where communicable diseases cannot be resolved, while non-communicable diseases, including asthma tend to increase. This Community Service aims to provide education to the public through health education needed to overcome the problem of infectious diseases in the community. In conclusion, this community service activity is that the counseling is going well and the advice to the counseling participants is that the community service counseling participants can do CERDIK which is a healthy life behavior that is able to keep people away from various non-communicable diseases (PTM) such as vascular disease, heart disease, and kidney problems . Likewise, the hope is that the community can take part in community activities in the form of Posbindu which are held every month in their respective areas.